Investigation of changes in protein composition of rye grain and oat grain during germination as the raw materials for baby food production - Maksimenko, A.; Bobel (Zinchenko), Inna; Terletska, Vita (My University, 2014)
In order to develop a balanced chemical composition of dry baby food product with the addition of malt we studied the chemical composition of raw components (rye and oat grain) and their changes during processing. Experiments were carried out with grains and fresh malt. As a result, studies have found that when grain is germinating the protein content of the grain is changing: the protein content of rye is reduced by 3% of dry matter, and in oats grain - 4.2% of dry matter. Mass fraction of amino nitrogen decreased slightly (by 2,8-3,2% of dry matter). Для того щоб розробити збалансований хімічний склад сухого продукту дитячого харчування з додаванням солоду ми вивчали хімічний склад сировинних компонентів (зерна жита і вівса) та їх змін в процесі оброблення. Експерименти проводили із зерном та свіжим солодом. Результати дослідження показали, що при пророщуванні вміст білка в зерні змінюється: вміст білка жита знижується на 3% СР, а в зерні вівса — 4,2% СР. Масова частка амінного азоту незначно знизилася (на 2,8-3,2% СР).
Keywords: protein composition; rye grain; oat grain; germination; склад білкових речовин; зерно жита; зерно вівса; пророщування; кафедра технології хлібопекарських і кондитерських виробів